Isolasi Biogeografis Ikan Kihung (Channa lucius) di Danau Rawoijo, Situs Bukit Bangkai, Kalimantan Selatan Berdasarkan Profil Jenis dan Bobot Protein - Tanto Budi Susilo; Nur Sobah; kamilia Mustikasari; Rani Sasmita (Bioscientiae, 2022)
This paper had described the protein profile of kihung or snakehead fish in Rawoijo Lake, the located east of the prehistorics sites, at Bukit Bangkai, South Kalimantan. There had not been many studies of the Kihung (Channa lucius) in this prehistoric sites. This information on protein profiles and weights had a strategic role in the management of the site area for educational and scientific tourism purposes. The analysis of kihung fish was carried out by describing morphology, morphometric and meristic calculations and comparison kihung fish from Banjar Regency, almost 400 Km from the Bukit Bangkai sites too.The protein content was measured by the Lowry method. Protein profiles were analyzed using the SDS-PAGE and elaborated using the UPGMA method. The results of morphological observations of kihung fish have a lighter body color and all fins are thick with regular patterns from Lake Rawoijo, while fish from Banjar Regency have a dark brownish body color. These fish have thin fins all with a pattern that is not irregular too. Optimum protein levels dissolved in kihung fish meat from Rawoijo, sample 1; 2; 3; 4; 5 which that was 2.117; 2,619; 2,931; 6,974; 7.601 mg/ml, and samples were 1,704, 2,874; 2,369; 1532; 1,921 mg/ml, respectively, from Banjar Regency. Based on identified the protein weight profile were fructose-bisphosphate aldolase A, aldolase, phophoglycerate kinase, creatine kinase, enolase, actinin, glutamic dehydrogenase, actin protein, desmin, and albumin. For the expression of fish protein bands from Lake Rawoijo had tend to be thicker than fish protein bands from Banjar Regency. The results of the dendogram construction of the UPGMA method showed that Kihung were more closely related to the intra group of Banjar fish itself and Kihung fish from Lake Rawoijo had formed an inter group. This information had shown one of the evidences that Kihung fish are experiencing a biogeographic isolation at Bukit Bangkai sites.